2020
DOI: 10.1101/2020.02.14.947846
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resolving a QTL complex for height, heading, and grain yield on chromosome 3A in bread wheat

Abstract: Crop height (Ht), heading date (Hd), and grain yield (GY) are interrelated traits in wheat. Independent manipulation of each is important for adaptation and performance. Validated QTL for all three collocate on chromosome 3A in the Avalon x Cadenza population. We asked if these are linked or pleiotropic effects. The region was dissected using recombinants derived from Near Isogenic Lines. It was shown that Ht and Hd are controlled by independent genes. The newly defined Ht QTL interval contained a gene cluster… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This variability reiterates the fact that these responses cannot be generalised across study systems and are thus context-dependent (Chitty & Gange, 2021). Modern crop breeding, which focuses chiefly on improving above-ground traits of wheat under optimal conditions for achieving high yields (Martinez et al, 2020), may provide an explanation. Over time, artificial selection has inadvertently restricted root characteristics of elite wheat (Voss-Fels et al, 2017), resulting in smaller root systems (den Herder et al, 2010), lower root-to-shoot ratios (Siddique et al, 1990) and reduced mycorrhizal responsiveness when compared to older varieties (Zhang et al, 2018), with modern wheat cultivars also known to supply AM fungi with fewer plant C resources than more derived plants (Field et al, 2012;Thirkell et al, 2019Thirkell et al, , 2021.…”
Section: Aphid Feeding Does Not Impact Am Colonisation or Mycorrhiza-...mentioning
confidence: 98%
“…This variability reiterates the fact that these responses cannot be generalised across study systems and are thus context-dependent (Chitty & Gange, 2021). Modern crop breeding, which focuses chiefly on improving above-ground traits of wheat under optimal conditions for achieving high yields (Martinez et al, 2020), may provide an explanation. Over time, artificial selection has inadvertently restricted root characteristics of elite wheat (Voss-Fels et al, 2017), resulting in smaller root systems (den Herder et al, 2010), lower root-to-shoot ratios (Siddique et al, 1990) and reduced mycorrhizal responsiveness when compared to older varieties (Zhang et al, 2018), with modern wheat cultivars also known to supply AM fungi with fewer plant C resources than more derived plants (Field et al, 2012;Thirkell et al, 2019Thirkell et al, , 2021.…”
Section: Aphid Feeding Does Not Impact Am Colonisation or Mycorrhiza-...mentioning
confidence: 98%
“…An additional QTL for DTH was identified in the Avalon x Cadenza population (U.K.) on chromosome arm 3AS around the peak marker BS00021976 (169 Mb RefSeq v1.0) (Martinez et al 2021). This QTL interval (60 Mb at each side of BS00021976) includes 536 annotated genes, among which the authors proposed FT-A2 as a candidate of particular interest.…”
Section: Ft-a2 As a Candidate Gene For Previously Published Sns Qtls On Chromosome Arm 3asmentioning
confidence: 99%
“…Using our FT-A2 marker, we established that both Avalon and Cadenza carry the A10 allele, so we conclude that the D10A polymorphism is not the cause for the observed QTL for DTH on 3AS in this population. Martinez et al (2021) suggested that differences in FT-A2 transcript levels may contribute to the differences in DTH, but more precise mapping of this QTL will be necessary to support this hypothesis.…”
Section: Ft-a2 As a Candidate Gene For Previously Published Sns Qtls On Chromosome Arm 3asmentioning
confidence: 99%
“…The physical positions of one of the genomic regions that we identified for heading on chromosome 5B (at 575.8 Mb) and the coincident region associated with both heading and GPC on 5A (at 586.5–588.6 Mb) coincided with the Vrn‐B1 and Vrn‐A1 genes, respectively. Coincident genomic regions and QTLs have been reported in several other studies (Babu et al., 2003; Lanceras et al., 2004; Quarrie et al., 2006; Pushpendra et al., 2007; Bai et al., 2013; Guan et al., 2018), which could be due to the pleiotropic effect (a single locus having effects on more than one trait simultaneously) or tight linkage (Tuberosa et al., 2002; Martinez et al., 2021).…”
Section: Discussionmentioning
confidence: 57%